PENGARUH INFLASI DAN NILAI TUKAR RUPIAH TERHADAP PERGERAKAN HARGA SAHAM PADA INDEKS SAHAM SYARIAH INDONESIA (ISSI) - Hairunnisa; Siti Maysaroh; Melati (LA RIBA: Jurnal Perbankan Syariah, 2021)
To move towards a more advanced economy, a sufficiently high economic growth must be supported by a low inflation rate and a stable exchange rate. Meanwhile, the main source of the increase in the financial balance is estimated to still be contributed by an increase in foreign direct investment (FDI). The development of the Indonesian Islamic capital market began with the issuance of Islamic mutual funds in 1997. However, the development of the Islamic capital market until the end of 2015 had not yet reached a significant share in the capital market industry. The approach used in this research is a quantitative approach. The statistical test used in the analysis is the multiple linear regression method. Inflation has a negative effect on the Indonesian Islamic stock index. The significant value is 0.0000 while the rupiah exchange rate has a positive influence on the Indonesian sharia stock index. The significant value of the rupiah exchange rate is 0.0006. The result of this test is that the probability value of F is less than , which is 0.000000 < 0.05. The conclusion of this study is that the inflation rate partially has a significant effect on stock price movements on the Indonesian Sharia Stock Index (ISSI), the rupiah exchange rate partially has a significant effect on the Indonesian Sharia Stock Index (ISSI) and simultaneously, the inflation rate and the rupiah exchange rate. significant effect on the Indonesian Sharia Stock Index (ISSI).